Fatty acid dynamics of the adductor muscle of live cockles (Cerastoderma edule) during their shelf-life and its relevance for traceability of geographic origin. (July 2017) - Ricardo, Fernando; Pimentel, Tânia; Maciel, Elisabete; Moreira, Ana S.P.; Rosário Domingues, M.; Calado, Ricardo
Abstract: Cockles ( Cerastoderma edule ) are commercially important bivalves that support several fisheries in European waters. The fatty acid (FA) profile of the adductor muscle (AM) of freshly collected live cockles can be used to reliably confirm their geographic origin. This approach is paramount for traceability, expose fraud and ensure food safety. However, no study has ever addressed if the FA profile of the AM of live cockles remains stable during shelf-life, as significant shifts may blur FA signatures recorded at harvest. The present study investigated the FA dynamics of the AM of live cockles during their shelf-life (seven days post-harvest under a refrigerated environment). Fatty acid methyl esters were obtained after transesterification of lipid extracts and analyzed through gas chromatography–mass spectrometry (GC–MS). Results indicated that FA profiles remained stable until the third day post-harvest. After this period cockles started to exhibit contrasting FA profiles on their AM, namely a higher percentage of heptadecanoic acid (17:0). This FA is associated with the growth of pathogenic microorganisms responsible for food spoilage. In this way, the FA profile of the AM of live cockles can be used to reliably trace geographic origin up to three days post-harvest, as long as specimens are stored under refrigerated conditions during shelf-life. Highlights: Fatty acid (FA) profiles of adductor muscle remain stable up to 3 days post-harvest. Cockles geographic origin can be traced using FA profiles up to 3 days post-harvest. 17:0 is a bacterial marker used as quality indicator for food spoilage. 17:0 is the main responsible for contrasting FA profiles along shelf life.